MSMEs Performance Besed on Knowledge and Business Capabilities - Tini Kartini; Endang Silaningsih; Dony Ferry Anggoro; Sudarijati Sudarijati (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This research aims to find out how knowledge and business abilities influence the performance of shoe micro, small and medium enterprises (MSMEs) in Kebon Kembang Market, Bogor City. All shoe MSME players in the market are the objects of research. In this study, the population was 48 business people. The sampling was 48 business people where the sample was determined through census or saturated sampling. This research uses quantitative methods. Data analysis uses various statistical tests, including validity, reliability tests, multiple linear regression tests, multiple correlation analysis, and coefficient of determination (R2). The results of the research show that knowledge and business abilities have quite a big influence on the performance of shoe MSMEs in the Kebon Kembang Market. Around 63.1% of MSME performance can be explained by knowledge and business ability factors. Knowledge and business abilities have a positive and significant effect on the performance of MSMEs, both simultaneously and partially.